Strategic Management Based on Cadet Education at SMAN 5 Taruna Brawijaya - Agus Suwandi, Eko; Zaenul Fitri, Agus (Journal of World Science, 2023)
The acceleration of information requires the public to demand educational attainment following the wishes and demands of the times. The Covid 19 pandemic should not be solely used as a single factor as a cause of the failure of educational institutions to defend themselves against the public trust. At present, the inability to understand the condition of educational institutions and market demands means that many institutions must close or merge to save their existence. This study uses qualitative methods, in-depth interview techniques, observation, and document excavation. Senior High School 5 Taruna Brawijaya is supported by the implementation of strategic management, which can be classified as work, namely, changing the vision, mission, and goals of the institution, sharpening the reading of internal and external challenges, implementing cadet-based school branding, implementing policies, and implementing financing policies. Senior High School 5 Taruna Brawijaya Kota Kediri has succeeded in becoming a driving school, and this has increased trust and competitiveness in the community.